The Mediating Role of Teachers' Digital Competence in the Relationship Between Curriculum Management and Smart Learning - Suratman Suratman; Sugiyono Sugiyono (Business and Applied Management Journal, 2025)
This study explores the mediating role of teachers' digital competence in the relationship between curriculum management and smart learning. Using a quantitative, correlational survey design, the study sampled 219 teachers from State Islamic Senior High Schools in Samarinda, selected via simple random sampling. Data were analysed using JASP V.0.16 for simple linear regression and mediation effects. The findings reveal positive and significant relationships between curriculum management and teachers' digital competence, curriculum management and smart learning, and teachers' digital competence and smart learning. Moreover, teachers' digital competence partially mediates the relationship between curriculum management and smart learning. These results highlight that effective curriculum management enhances teachers' readiness to utilise digital technology and directly contributes to the successful implementation of smart learning in madrasahs. This research provides insights into improving curriculum management practices to enhance digital competence and facilitate smart learning.